Study of the Relationship between Economic Growth and Inflation: Application to the Countries of the South Side of the Mediterranean: A Panel Data Approach - Kaouther, Amiri; Besma, Talbi (Journal of Social Economics Research, 2014)
This paper examines the relationship between economic growth and inflation taking into account other economic indicators in the analysis of this relationship. This study uses the random effects model of panel data applied to a sample of four countries on the south side of the Mediterranean during the period that runs from 1980 to 2008. The analysis concludes that, in general, the relationship between the variables appears particularly if inflation or hyper-inflation. Indeed, if a country prices rise faster than in other countries, we will see an increase in imports and a decline in exports. To balance the balance of payments, it will attract the foreign exchange reserves.